Animasi 2D Corona Virus Desease 19 (Covid 19) Sebagai Media Edukasi Anak - Anak - Nur Budi Nugraha; Tri Yuliati (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
The development of technology is currently growing very rapidly making it easier for the community to convey information. 2D animation can be a means of socialization for the sake of interesting and efficient information. In the midst of the widespread Covid-19 outbreak in Indonesia, the government took several steps to minimize the spread of Covid-19 by socializing including to schools. The school always reminds its students to comply with health protocols. However, less interesting socialization makes children less enthusiastic in understanding the purpose of socialization. The purpose of this research is to make a 2D animated video about Covid-19. This 2D animated video is made as attractive as possible with characters and sound effects that children like so that children become interested in learning and understanding about covid-19. Based on the results of this educational media test, it has been tested on children and helps children in the process of delivering information about covid 19 more effectively and interestingly. Of the 20 respondents, 60% (12 people) agreed that animated videos help children understand covid 19